2022
DOI: 10.21037/acs-2022-rmvs-22
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of mid-term survival, reoperation, and recurrent mitral regurgitation for robotic-assisted mitral valve repair

Abstract: Background: Over the past two decades surgical approaches for mitral valve (MV) disease have evolved with the advent of minimally invasive techniques. Robotic mitral valve repair (RMVr) safety and efficacy has been well documented, however, mid-to long-term data are limited. The aim of this review was to provide a comprehensive analysis of the available mid-to long-term data for RMVr.Methods: Electronic searches of five databases were performed to identify all relevant studies reporting minimum five-year data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
(106 reference statements)
1
6
0
Order By: Relevance
“…Two patients required conversion to sternotomy (1.4%) and eight patients required PPM insertion (3.7%). Even with small patient numbers, these results are consistent with previously published data assessing robotic mitral valve surgery ( 24 ). One explanation for this is the exclusion of higher risk patients from robotic mitral valve cohorts, such as those with elevated body mass index (BMI), difficult access, reoperation and pulmonary disease.…”
Section: Discussionsupporting
confidence: 91%
“…Two patients required conversion to sternotomy (1.4%) and eight patients required PPM insertion (3.7%). Even with small patient numbers, these results are consistent with previously published data assessing robotic mitral valve surgery ( 24 ). One explanation for this is the exclusion of higher risk patients from robotic mitral valve cohorts, such as those with elevated body mass index (BMI), difficult access, reoperation and pulmonary disease.…”
Section: Discussionsupporting
confidence: 91%
“…A recent meta-analysis including 9 studies and 3,300 patients undergoing robotic MVRp revealed that the rates of overall survival at 1, 5, and 10 years were 99.2%, 97.4%, and 92.3%, respectively. 26 Freedom from mitral valve reoperation at 8 years after robotic MVRp was 95.0%. Freedom from moderate or severe recurrent MR at 7 years was 86.0%.…”
Section: Commentsmentioning
confidence: 92%
“…Centers with expertise in robotic MV repair have obtained equal results (quality) with less morbidity (cost), and therefore more value (value = quality/cost) for their patients. 16 , 17 , 18 , 19 , 20 , 21 , 22 However, as illuminated by the aforementioned points, there are more subtle benefits from robotics fostering a more enlightened approach to MV reconstruction. 23 …”
Section: Enlightenmentmentioning
confidence: 99%